Teen Dating Violence in a High-Risk Sample: The Protective Role of Maternal Acceptance. Issue 19 (October 2021) - Livingston, Jennifer A.; Lessard, Jared; Casey, Meghan L.; Leonard, Kenneth E.; Eiden, Rina D.
Exposure to marital conflict has been identified as a risk factor for teen dating violence (TDV). Given the high rates of marital conflict observed in families affected by paternal alcoholism, children of alcoholic fathers may be at increased risk for TDV. Positive parenting behaviors are protective against TDV in general, but whether they can attenuate the effects of exposure to marital conflict is uncertain. According to social learning theory, adolescents exposed to both positive and conflictual parenting may perceive aggression to be part of a normal and loving relationship and hence be at risk for TDV. In contrast, attachment theory would posit that positive parenting would better enable youth to regulate negative emotions and would be protective against TDV. The current study used prospective data to examine whether maternal acceptance buffered the relationship between exposure to marital conflict in early adolescence and TDV in late adolescence among a sample of adolescents at risk for TDV due to parental alcoholism. Adolescents ( N = 227, 50% female, 89% European American), half of whom had an alcoholic parent, completed surveys in early (eighth grade) and late adolescence (11th and 12th grades). They reported on exposure to marital conflict, perceptions of maternal acceptance, and involvement in TDV. Regression analyses revealed that exposure to marital conflict in early adolescence was predictive of TDV in late adolescence. However, an examination of the interaction between exposure to marital conflict and maternal acceptance indicated that at high levels of marital conflict and maternal acceptance, exposure to marital conflict no longer predicted TDV. Findings suggest that social modeling alone is not sufficient for understanding the intergenerational transmission of violence. A multipronged approach to violence prevention among high-risk families targeting both parental and parent–child relationships is recommended.